THE RELATIONSHIP BETWEEN PSYCHOLOGICAL CHARACTERISTICS AND BURNOUT SYNDROME AMONG DEPARTMENTAL UNIVERSITIES TEACHERS - Kolesnikova, Natalia; Makarkina, Oksana; Dvoretsky, Dmitry; Dyatlov, Yuriy; Manoylova, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article deals with the results of the study on burnout syndrome among teachers with various work experiences in university. The aim of the study is the review of burnout psychological patterns among teachers with various work experiences in university. The main hypothesis of the study is based on the assumption that the teachers whose work experience in departmental universities is more than 10 years are more vulnerable to the burnout syndrome development. In order to attain the envisaged goals and to test the hypothesis there were used empirical methods: differential diagnosis of decreased functioning by A. Leonova and S. Velichkovskaya, diagnosis of professional burnout by K. Maslach and S. Jackson adapted by N.E. Vodop’yanova, technique for diagnosing the burnout syndrome level by V.V. Boiko. Group comparison of teachers with various work experiences in university has shown that long term professional activity leads to burnout syndrome development: the most part of examined teachers are characterized by high level of burnout syndrome which structure is observed in high intensity of resistance and exhaustion phases and such syndromes as inadequate emotional discrete response; resignation or depersonalization, emotional and moral disorientation; psychosomatic and vegetative disorders.